Failure Analysis and Countermeasures of Conveyor Chains for Zinc Ingot Casting Machines - Lu Jianfu; Huang Qing; Shou Qifeng; Zhang Jinyong; Shou Yulai; Shou Nan (Jixie chuandong)
Based on the casting process of zinc ingots, the service condition and structure of the conveyor chain, the failure causes of the conveyor chain are analyzed in detail. By improving the structure and lubrication condition of the roller, the foreign matter can be controlled to invade the rotating pair, and the friction resistance of the chain running is reduced. 35CrMo and 20CrMo are used as a pin-bush hinge pair material under heavy load, dust and higher temperature conditions, and the anti-wear ability of a hinge pair is improved by adopting reasonable heat treatment process and lubrication method. The extruding hole and shot peening technology are adopted for the chain plate, and the interference amount of the special-shaped fit between the pin and the outer-plate is appropriately selected, which can enhance the anti-fretting damage ability of the joint between the pin and the outer-plate. The application effects show that the countermeasures proposed can improve the joint fastness between the pin and the outer-plate, ensure a rigid frame of the outer link, and effectively improve the service life and smooth operation of the chain.